Transfer of creditor’s right to claim in obligations of execution of work or provision of services to guarantor - Pohrebniak, Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The author attends to a problem of transfer of creditor’s right in obligation secured with bail to guarantor who exercised the debtor’s obligation. Analyzes of appropriate problem is conducted in context of juridical construction of relationship of execution of work and provision of services and within research of juridical mechanism of appropriate legal possibilities transfer.The provisions of current civil legislation are provide that in cases when debtor break an obligation secured with bail such debtor and guarantor become solidary debtors before creditor. The guarantor who has exercised debtor’s obligation acquires creditor’s rights in relationship secured with bail. In view of appropriate legislative provisions the author raises a problem of content of appropriate civil rights that transfer to guarantor. It is defined that in relationships of execution of work or provision of services an executor (debtor) obliged to provide a service or execute a work and client (creditor) has a right to claim execution of debtor’s obligation. In these cases execution of debtor’s obligation by guarantor terminates such obligation that causes termination of appropriate right of creditor. As a result the guarantor can’t acquire appropriate right of creditor because it is doesn’t exist.In light of such problem the author constructs theoretical model of juridical scheme that can justify appropriate legal mechanism of transfer of right to claim. As a result of comprehension of researched construction the author concludes that guarantor can acquire creditor’s rights in obligation secured with bail in particular in cases when he doesn’t exercise the obligation of debtor but exercise out of relationship the behavior that is identical to such obligation by its content. In return of such behavior that is useful for creditor the guarantor acquire creditor’s rights in appropriate relationship.Seeing difficulties and in some cases impossibility of application of p. 1 of art. 556 of Civil Code of Ukraine the author make conclusion that p. 1 of art. 544 of Civil Code of Ukraine need to be applied to relationships that arise between creditor, debtor and guarantor.